The Application of Induced Pluripotent Stem Cells Against Liver Diseases: An Update and a Review - Zhang, Lei; Pu, Ke; Liu, Xiaojun; Bae, Sarah Da Won; Nguyen, Romario; Bai, Suyang; Li, Yi; Qiao, Liang (Frontiers in Medicine, 2021)
Liver diseases are a major health concern globally, and are associated with poor survival and prognosis of patients. This creates the need for patients to accept the main alternative treatment of liver transplantation to prevent progression to end-stage liver disease. Investigation of the molecular mechanisms underpinning complex liver diseases and their pathology is an emerging goal of stem cell scope. Human induced pluripotent stem cells (hiPSCs) derived from somatic cells are a promising alternative approach to the treatment of liver disease, and a prospective model for studying complex liver diseases. Here, we review hiPSC technology of cell reprogramming and differentiation, and discuss the potential application of hiPSC-derived liver cells, such as hepatocytes and cholangiocytes, in refractory liver-disease modeling and treatment, and drug screening and toxicity testing. We also consider hiPSC safety in clinical applications, based on genomic and epigenetic alterations, tumorigenicity, and immunogenicity.